Evaluation of the Effectiveness of Vaccination of Russian Railways employees - N. A. Kostenko; E. A. Jidkova; A. A. Goriaev; I. V. Shangin; D. A. Khaltourina; Y. N. Matveyev; V. V. Ustyuzhanin; K. G. Gurevich (Эпидемиология и вакцинопрофилактика)
Relevance. The effectiveness of vaccination of the working population against COVID-19 in the Russian background has not been studied enough.Aim. To evaluate the effectiveness of vaccination of the working population with Gam-COVID-Vak (Sputnik V) in the Russian Railways as an example.Materials & Methods.The effectiveness of vaccination with Sputnik V among employees of Russian Railways in the period from January 21 to November 31, 2021 was performed with the Cox regression method.Results. The effectiveness of Sputnik V against COVID-19 infection with was 97.8% (95% CI 97.8–97.9%) for two doses, 91.9% (95% CI 91.6–92.2%) for a single dose, and 97.9% (95% CI 97.6–98.1%) for revaccination, all after socio-demographic factors adjusted. The effectiveness of vaccination against COVID-19 with hospitalization was 97.5% for two doses of Sputnik V (95% CI 97.1–97.9%), 86.1% (95% CI 83.7–88.1%) for a single dose, and 98.2% (95% CI 96.3–99.2%) for revaccination. The effectiveness against lethal COVID-19 was 95.2% (95% CI 93.1–96.6%) for two doses of Sputnik V and 94.8% (95% CI 89–97.6%) for one dose. The high efficiency of vaccination could be associated with a fairly young age composition of the employees of the Russian Railways.Conclusions. The study showed the high effectiveness of vaccination with Sputnik V against COVID-19 among the working population.